2017
DOI: 10.1097/md.0000000000006242
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum ALT and T-cell receptor beta variable chain for HBeAg seroconversion in chronic hepatitis B patients during tenofovir treatment

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Several serum markers, such as HBV DNA, quantitative HBsAg, and alanine aminotransferase (ALT), have been identified as predictors of Peg-IFN or NUC treatment outcome in the early treatment stage (Martinot-Peignoux et al, 2013;Yang et al, 2017). Recently, serum HBV RNA was proposed as a useful viral marker for CHB during therapy (Gao et al, 2017;Giersch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several serum markers, such as HBV DNA, quantitative HBsAg, and alanine aminotransferase (ALT), have been identified as predictors of Peg-IFN or NUC treatment outcome in the early treatment stage (Martinot-Peignoux et al, 2013;Yang et al, 2017). Recently, serum HBV RNA was proposed as a useful viral marker for CHB during therapy (Gao et al, 2017;Giersch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In detail, all subjects were orally treated with 300 mg of TDF-naive daily and were scheduled to continue the TDF treatment for 96 weeks. The twenty HBeAg (+) CHB subjects were divided into HBeAg seroconverting (SC, n = 9) or non-SC ( n = 11) groups, depending on whether they had undergone HBeAg SC by week 72 of TDF treatment, that was HBeAg loss (quantitative HBeAg < 0.18 PEIU/mL) and positive for anti-HBe antibody (quantitative anti-HBe < 1.00 S/CO) [ 20 ]. This protocol was approved by the ethics committee of the FHZJU (Reference No.…”
Section: Methodsmentioning
confidence: 99%
“…BV12, BV15, and BV22 were predominant in the patients who had not seroconverted. In addition to the Treg frequency and alanine aminotransferase (ALT) level, the Treg profile and TRBVs were associated with HBeAg seroconversion and may be potential predictors of HBeAg seroconversion and treatment outcome in CHB patients[ 55 , 56 ]. A recent TCR repertoire study by Lian et al [ 57 ] in 20 CHB patients undergoing 1-year ETV treatment found that the diversity of TCRβ repertoires was decreased in the 10 HBeAg- seroconverted patients but increased in the 10 patients without HBeAg seroconversion.…”
Section: Application Of Immune Repertoire Analysis In Hbv Therapymentioning
confidence: 99%